1994
DOI: 10.1073/pnas.91.21.9789
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a mammary transforming gene (MAT1) associated with mouse mammary carcinogenesis.

Abstract: We have developed an eent in vitro transformation system using N-methyl-N-nitrosourea that aflows us to study the role of hormones and growth factors in mouse mammary tumorigenesis. Ulizing this system, we reported earlier that mammary tumors induced in vitro with N-methyl-N-nitrosourea in the presence of mamogenic hormones (progesterone and prolactin) contain predominately an activated c-Ki-ras protooncogene with a G35 --A35 transitional mutation in the 12th codon. Mammary tumors induced in the presence of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 24 publications
0
19
0
1
Order By: Relevance
“…The final 1050 bases of this region are 70% identical to MAT1, a transforming cDNA isolated from a lithium-induced mouse mammary tumor (27). To determine whether the 3Ј-UTR is necessary for the reversal of Ha-Ras integrin suppression, we tested a construct without this sequence and found that it functioned like the full-length cDNA (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…The final 1050 bases of this region are 70% identical to MAT1, a transforming cDNA isolated from a lithium-induced mouse mammary tumor (27). To determine whether the 3Ј-UTR is necessary for the reversal of Ha-Ras integrin suppression, we tested a construct without this sequence and found that it functioned like the full-length cDNA (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…One explanation for this apparent discrepancy could be that the 2.4-kb cDNA for PEA15 contains the entire sequence from the proto-oncogene MAT1, and deregulation of this MAT1 region may contribute to the apparent tumorigenicity of PEA15 (Estelles et al, 1996). MAT1 is known to neoplastically transform NIH3T3 mouse fibroblasts and the mammary epithelial cell line TM3 (Bera et al, 1994). Another study reported that the human homolog of MAT1 (hMAT1) was expressed in the human breast cancer cell lines MDA-MB-231, BT20, and T47D at levels 10 times higher than those in normal human mammary epithelial cells (Hwang et al, 1997); this difference in hMAT1 expression level may be partly responsible for the tumorigenicity of MDA-MB-231 and BT20 cells.…”
Section: Discussionmentioning
confidence: 99%
“…PEA-15 contains the mammary transforming (MAT1) proto-oncogene in the 3 0 untranslated region of the 2.5 kb splice form (Bera et al, 1994;Tsukamoto et al, 2000). The MAT1-containing PEA-15 mRNA is expressed weakly during certain physiological circumstances, but becomes strongly expressed in murine mammary tumors and squamous carcinoma cells (Dong et al, 2001).…”
Section: Pea-15/pedmentioning
confidence: 99%